Working children - Saller, Carol (Minneapolis : Carolrhoda Books, 1998)
Describes the various jobs which children performed during the early 1900s, the reasons for employment, working conditions, the efforts of reformers, and child labor today.
Includes bibliographical index.
Keywords: Child labor -- History -- Juvenile literature -- United States; Child labor